2024
DOI: 10.1111/anae.16220
|View full text |Cite
|
Sign up to set email alerts
|

Impact of postoperative cardiovascular complications on 30‐day mortality after major abdominal surgery: an international prospective cohort study

Abstract: SummaryCardiovascular complications after major surgery are associated with increases in morbidity and mortality. There is confusion over definitions of cardiac injury or complications, and variability in the assessment and management of patients. This international prospective cohort study aimed to define the incidence and timing of these complications and to investigate their impact on 30‐day all‐cause mortality. We performed a prospective, international cohort study between January 2022 and May 2022. Data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…We found the article by Mulier et al intriguing [1]. The authors cited our data [2] to estimate sevoflurane loss due to system leak in anaesthesia machines during maintenance of general anaesthesia.…”
Section: Variation In the Amount Of Leakage Containing Inhalational A...mentioning
confidence: 93%
See 2 more Smart Citations
“…We found the article by Mulier et al intriguing [1]. The authors cited our data [2] to estimate sevoflurane loss due to system leak in anaesthesia machines during maintenance of general anaesthesia.…”
Section: Variation In the Amount Of Leakage Containing Inhalational A...mentioning
confidence: 93%
“…The international, prospective cohort study (CArdiovaSCulAr outcomes after major abDominal surgEry, CASCADE) reported that postoperative cardiovascular complications, as defined by the Standardised Endpoints for Perioperative Medicine-Core Outcome Measures for Perioperative and Anaesthetic Care (StEP-COMPAC), occurred infrequently in patients undergoing major abdominal surgery (incidence 2.5%), but that 1 in 5 postoperative deaths were attributable to these complications [1]. Despite these important findings, we have reservations regarding the methodology and conclusions of this study.…”
Section: Incidence and Impact Of Cardiovascular Complications After M...mentioning
confidence: 99%
See 1 more Smart Citation